Menggerakan Ekonomi Lokal Melalui Ecopreneurship: Inisiatif Pemberdayaan Karang Taruna Di Kecamatam Sumbermulyo Lampung (Praktek Pembuatan Lilin Dari Minyak Jelantah Dan Pengaharum Ruangan Aroma Terapi) - Febrianty, Febrianty; Pratama, Muhammad Irfan; Sejati, Hiro; Muhammad, Muhammad (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2024)
Promoting local economic development through an ecopreneurship approach serves as an innovative solution to empower communities, particularly the younger generation. This study examines the empowerment initiatives undertaken by Karang Taruna in Sumbermulyo Subdistrict, Lampung, through the practices of making candles from used cooking oil and producing aromatherapy air fresheners. These activities aim to provide new skills, create eco-friendly business opportunities, and raise community awareness about household waste management. The process of making candles from used cooking oil involves a simple, effective, and easily applicable recycling method. Meanwhile, the aromatherapy air fresheners are crafted using natural materials readily available in the surrounding environment. This program not only generates economic benefits for Karang Taruna members but also contributes to waste reduction and environmental quality improvement. The results indicate that this ecopreneurship approach successfully enhances entrepreneurial skills, motivates young people to engage in entrepreneurship, and delivers positive socio-economic impacts for the Sumbermulyo community. Thus, this initiative serves as a model for community empowerment that can be adopted by other communities to sustainably stimulate local economic growth.Keywords: Ecopreneurship, Community Empowerment, Karang Taruna, Local Economy, Recycling, Used Cooking Oil.